Study of antioxidant and xanthine oxidase inhibitory activities of Cascabela thevatia and Coriandrum sativum - Subba, Bimala; Rijal, Sarita; Kharel, Prabhat (Scientific World, 2025)
Two traditionally used medicinal plants, Cascabele. thevatia and Coriandrum sativum, were chosen for this investigation, and their bioactive components and xanthine oxidase inhibitory potential were examined. The phytochemical screening of the investigated plant leaf extracts revealed that these plants contain a wealth of secondary metabolites such as alkaloids, flavonoids, phenols, saponins, and terepenoids, among other things. Calculations of total phenol content (TPC) and total flavonoids content (TFC) values in plant extracts revealed that C. thevatia contained the greater values of TPC (75.21 mg GAE/g) and TFC (69.09 mg QE/g). Both leaf extracts exhibited significant antioxidant activity comparable to that of standard ascorbic acid, as evidenced by the DPPH and FRAP assays.The methanol leaf extract of C. thevatia, with an IC50 value of 26.1±1.51 mg/mL, had the highest xanthine oxidase inhibitory activity between studied plants, making it an effective antigout agent. The findings provide scientific support for the use of C. thevatia and C. sativum, both of Nepalese origin, in traditional medicine to treat gout. This is the first study to show that C. thevatia leaf extract inhibits xanthine oxidase. This study may provide useful data for future research.